2021
DOI: 10.1007/978-3-030-68285-9_6
|View full text |Cite|
|
Sign up to set email alerts
|

Digital Transformation in Higher Education: Maturity and Challenges Post COVID-19

Abstract: Digital transformation in higher education, especially after COVID-19 is inevitable. This research explores digital transformation maturity and challenges post COVID-19. The significance of the study does not only stem from the critical role of higher education in building the workforce and knowledge economy. This study triangulates the findings of multiple research instruments, including survey, interviews, case study, and direct observation. The research findings show a significant variance between the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…The previous study that was conducted by Kalolo [26] on several higher education institutions in developing countries showed that the lack of human resources became the main problem in the higher education institution that will implement the digital transformation, especially in the effort to move and integrate the digital technology in teaching-learning activities. The study is in line with what has been shown by Marks et al [10], Schaffhauser [19], and Rafiq et al [21] who also confirmed that the availability of resources with technical skills in the innovation of the education system is scarce.…”
Section: Resources 1) Expertssupporting
confidence: 91%
See 3 more Smart Citations
“…The previous study that was conducted by Kalolo [26] on several higher education institutions in developing countries showed that the lack of human resources became the main problem in the higher education institution that will implement the digital transformation, especially in the effort to move and integrate the digital technology in teaching-learning activities. The study is in line with what has been shown by Marks et al [10], Schaffhauser [19], and Rafiq et al [21] who also confirmed that the availability of resources with technical skills in the innovation of the education system is scarce.…”
Section: Resources 1) Expertssupporting
confidence: 91%
“…A study by Mark et al [10] found that most higher education institutions did not have a holistic vision of digital transformation yet. In addition, they lack the support and skill to form and deciding the most suitable new vision to achieve the success of the implementation of digital transformation is a barrier to the higher education institution [15], [16].…”
Section: A Vision 1) Clarity Visionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, they do not need to wait in a long queue compared to physical time attendance systems. It was confirmed in Marks et al (2021) that digital transformation during and post-COVID-19 should be carefully done, since there are a number of information technology (IT), security, and health safety challenges, but people are not aware of this holistic vision. In the final step, a user will give their consent related to data privacy.…”
Section: Discussionmentioning
confidence: 99%